2019
DOI: 10.3390/met9030367
|View full text |Cite
|
Sign up to set email alerts
|

Strain Hardening, Damage and Fracture Behavior of Al-Added High Mn TWIP Steels

Abstract: The strain hardening and damage behavior of Al-added twinning induced plasticity (TWIP) steels were investigated. The study was focused on comparing two different alloying concepts by varying C and Mn contents with stacking fault energy (SFE) values of 24 mJ/m 2 and 29 mJ/m 2 . The evolution of microstructure, deformation mechanisms and micro-cracks development with increasing deformation was analyzed. Al-addition has led to the decrease of C diffusivity and reduction in tendency for Mn-C short-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 47 publications
0
11
0
1
Order By: Relevance
“…Al delays the reorientation of Mn-C point defect complexes by rising the process activation energy [28,[31][32][33][34]. Song et al [35] and Madivala et al [36] reported that some amount of Al addition could suppress the Mn-C formation in high-Mn steels. This might be the reason for the delay or absence of the serration phenomenon in Al-alloyed high-Mn steels.…”
Section: Theories Explaining the Plc Mechanism In Medium-and High-manmentioning
confidence: 99%
“…Al delays the reorientation of Mn-C point defect complexes by rising the process activation energy [28,[31][32][33][34]. Song et al [35] and Madivala et al [36] reported that some amount of Al addition could suppress the Mn-C formation in high-Mn steels. This might be the reason for the delay or absence of the serration phenomenon in Al-alloyed high-Mn steels.…”
Section: Theories Explaining the Plc Mechanism In Medium-and High-manmentioning
confidence: 99%
“…For decades, high manganese steel has been studied for the application of automotive frame due to its excellent strength-ductility combination from the early stage of development [1][2][3][4][5][6][7]. Recently high manganese steel was tried to be applied for slurry pipes due to its excellent wear resistance.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the grains presented in this figure, several other grains and orientations were checked, and no twinning evidence was observed. The overall mechanical behavior of all three alloys were similar regardless of their SFE value, especially the work hardening rate curve, which is highly associated to the dislocation structure and the high capacity of such materials to store dislocations [2]. The SFE for the 0Al alloy was predicted by thermodynamic modeling (31 mJ/m²) and determined experimentally (28 ± 9 mJ/m²), which is the lowest value amongst the alloys studied here.…”
Section: Tensile Testsmentioning
confidence: 60%
“…High-Mn steels can be classified as Advanced High-Strength Steels (AHSS) and their development has been focused on understanding the exceptional mechanical properties, especially the ductility that can be achieved for such alloys [1,2]. The presence of plasticity-induced mechanisms has been described as one of the main contributions; however, the outstanding combination of high ductility and strength also arise because of the high capacity of the material to store dislocations in the microstructure [3].…”
Section: Introductionmentioning
confidence: 99%